Moral Formation as Transformation: The Contribution of Dietrich Bonhoeffer - Pope, Stephen J. (Studies in Christian-Jewish Relations, 2011)
This essay was delivered during a panel discussion entitled "The Formation of the Religious Conscience after the Shoah: Bonhoeffer’s Spirituality for Today " during the conference Dietrich Bonhoeffer for Our Times: Jewish and Christian Perspectives, cosponsored by the Center for Christian-Jewish Learning at Boston College, the United States Holocaust Memorial Museum, Hebrew College, and Andover-Newton Theological School, September 17, 2006. The author argues that Bonhoeffer can help us understand moral formation as personal and social transformation.